(untitled) (Global Journals of Research in Engineering, 2012)
An experimental investigation has been conducted to study the mechanical as well as micro structural properties of Recycled aggregate concrete (RAC) with uncoated and Geopolymer / Cement coated recycled aggregate exposed to elevated temperature. Fly ash (as replacement of cement) was added while making concrete. Cubes test specimens were prepared and cured under water for 28 days. Test specimens were exposed to different levels of temperature (400oC, 600oC, 800oC ) for a period of 6 hours in the muffle furnace. The reduction in compressive strength was observed are in the ranges from 23.4% to as high as 50.3% when exposed to different elevated temperature. MIP (Mercury intrusion porosimetry ) test was conducted to estimate the pore diameter and also to appreciate the change of total pore volume due to change of exposure temperature. SEM (Scanning electron microscopy) study was also done to appreciate the micro-structural change in recycled aggregate concrete.